Synthesis of 1- and 4-substituted piperazin-2-ones via Jocic-type reactions with N-substituted diamines. Issue 8 (7th January 2015) - Perryman, Michael S.; Earl, Matthew W. M.; Greatorex, Sam; Clarkson, Guy J.; Fox, David J.
Abstract : Enantiomerically-enriched trichloromethyl-containing alcohols are transformed regioselectively into enantiomerically-enriched 1-substituted piperazinones by modified Jocic reactions. Abstract : Enantiomerically-enriched trichloromethyl-containing alcohols, obtained by asymmetric reduction, can be transformed regioselectively into 1-substituted piperazinones by modified Jocic reactions with little or no loss of stereochemical integrity. This methodology can be easily used to synthesise important pharmaceutical compounds such as the fluorobenzyl intermediate of a known PGGTase-I inhibitor.